lncRNA SNHG15 as a ceRNA modulates Osteoclast Differentiation, Proliferation, and Metastasis by Sponging miR-381-3p/NEK2 Axis - YiFan Wang; GuanYin Zhu; Fang Pei; ZhiHe Zhao (Journal of Immunology Research)
Background. A growing number of studies have shown that long noncoding RNAs play an important role in osteoclast differentiation. However, there are few studies on the roles of lncRNA small nucleolar RNA host gene 15 (SNHG15) in osteoclast differentiation. Methods. The expressions of SNHG15, miR-381-3p, and never in mitosis-related kinase 2 (NEK2) mRNA were detected by real-time quantitative polymerase chain reaction (RT-qPCR); Western blot detected NEK2 and osteoclast markers (Cathepsin K, CTSK), matrix metalloproteinase 9 (MMP9), nuclear factor of activated T cell 2 (NFAT2), and tartrate-resistant acid phosphatase (TRAP) protein levels; cell proliferation was detected by Cell Counting Kit-8 (CCK-8), and the formation of osteoclasts was observed by TRAP staining; the F-actin skeleton was stained with tetramethylrhodamine isothiocyanate (TRITC) phalloidin; cell migration rate was detected by Transwell; dual-luciferase reporter gene assay and RNA-binding protein immunoprecipitation (RIP) assay verified the targeting relationship between miR-381-3p, SNHG15, and NEK2. Results. The expression of SNHG15 was increased in THP-1 cells stimulated by macrophage colony-stimulating factor (M-CSF)/receptor activator of nuclear factor-kappa B ligand (RANKL). Overexpression of SNHG15 significantly promoted the proliferation, migration, osteoclast differentiation, and expression of osteoclast markers CTSK, MMP9, NFAT2, and TRAP of THP-1 cells induced by M-CSF/RANKL. Knockdown of SNHG15 reversed this effect. Overexpression of SNHG15 downregulated the inhibitory effect of overexpression of miR-381-3p on the proliferation, migration, and differentiation of THP-1 cells induced by M-CSF/RANKL. Knockdown of miR-381-3p reversed the inhibitory effect of knockdown of NEK2 on the proliferation, migration, and differentiation of THP-1 cells induced by M-CSF/RANKL. Conclusion. SNHG15 acted as a ceRNA promoted the proliferation, migration, and differentiation of THP-1 cells induced by M-CSF/RANKL through sponging miR-381-3p to promote the expression of NEK2.